PENGARUH POSTUR KERJA TERHADAP KELUHAN MUSKULOSKELETAL PADA PEKERJA BATU BATA (Studi Kasus di Desa Kasreman Kecamatan Kandangan Kabupaten Kediri Tahun 2021) - Sarah Nurizha Aqilla; Setiawan .; Winarko . (Poltekkes Kemenkes Surabaya, 2022)
The brick industry is an industry where almost all of the processes are done traditionally. Workers' body postures when working are often not ergonomic, so there is a risk of causing muskuloskeletal complaints. This study aims to determine the effect of work posture on musculoskeletal complaints in brick industry workers in Kasreman Village, Kandangan District, Kediri Regency.This type of research is analytic observational with a cross-sectional approach. This study includes a population study with the entire population as a sample of 57 people. Data were collected by observing work postures using the Ovako Working Analysis System (OWAS) method and interviews about musculoskeletal complaints felt by workers using the Nordic Body Map (NBM) questionnaire. The data were analyzed univariately and bivariately with Chi Square test and continued with Fisher's Exact.The results of this study indicate that most of the workers have a high category of work posture, aged 35 years, and have high category of musculoskeletal complaints. Statistical test results show that there is an effect of work posture and age on musculoskeletal complaints in brick industry workers in Kasreman Village, Kandangan District, Kediri Regency in 2021.It is recommended for workers to pay attention to their work postures, adjust work and rest times, and stretch muscles. Industrial owners should pay more attention to workplace conditions, arrange work and rest times, and be able to provide sufficient and shady land to rest.